Concise Review: The Role of C-kit Expressing Cells in Heart Repair at the Neonatal and Adult Stage. (17th June 2014) - Hesse, Michael; Fleischmann, Bernd K.; Kotlikoff, Michael I.
Abstract : Ischemic heart disease is the number one cause of morbidity and mortality in the developed world due to the inability of the heart to replace lost myocytes. The cause of postinfarction myogenic failure has been a subject of intense scientific investigation and much controversy. Recent data indicate a brief perinatal developmental window exists during which postinfarction myogenesis, and substantial heart regeneration, occurs. By contrast, repair of an equivalent injury of the adult heart results in prominent revascularization without myogenesis. Here, we review recent experiments on neonatal postinjury myogenesis, examine the mechanistic hypotheses of dedifferentiation and precursor expansion, and discuss experiments indicating that postinfarction revascularization derives primarily from cardiac vascular precursors. These data have profound consequences for the understanding of human heart repair, as they address the long standing question as to whether human postinfarction myogenic failure is due to the loss of precursors existent at the neonatal stage or to a context-dependent inhibition of these precursors within the infarct, and suggest strategies for the recapitulation of neonatal myogenic capacity and the augmentation of revascularization. Stem Cells   2014;32:1701–1712